Nathan's fishing trip - Delacre, Lulu. (New York : Scholastic, 1988)
Nicholas Alexander takes Nathan on his first fishing trip, but after great difficulty in catching a trout, they haven't got the heart to eat it.
"A Lucas Evans book"--Verso t.p.
Booklist
2.0
K-3
Keywords: Fishing -- Fiction; Elephants -- Fiction; Mice -- Fiction; Fishing -- Fiction; Elephants -- Fiction; Mice -- Fiction